Combined 624-nm and 850-nm illumination at low rates leads to enhanced inhibition of Candida albicans - Guffey, J. Stephen; Payne, William C.; Qian, Zhuoyuan; Martin, Kyle A.; James, Leslie N.; Dodson, Carly M. (International Journal of Research in Medical Sciences, 2017)
Background: To determine whether combinations of red and infrared light could improve inhibition of Candida albicans and whether combining wavelengths and altering rate of energy delivery could prevent the formation of resistance to light energy. Methods: C. albicans was tested because of the common appearance in human skin and mucous membrane infections. The organism was treated in vitro with a combination of 624-nm (red) and 850-nm (infrared) light emitted from a supraluminous diode (SLD) array. Doses of 9, and 30 J/cm2 were used. Rate of energy delivery was also manipulated. Colony counts were performed and compared to untreated controls using Student t tests and one-way ANOVA with Tukey post hoc analysis. Results: The combination of 624 and 850-nm light energy at 30 J/cm2 was an effective (p ≤ 0.05) inhibitor of C. albicans across all seven stages of the experiment. The combination of 624 and 850-nm wavelengths produced a maximum kill rate [control – treated / control X 100] of 76.24% and an average kill rate of 54% across the seven stages of the experiment. Conclusions: A Combination of 624-nm and 850-nm light from an SLD array can inhibit the growth of C. albicans in vitro. Altering delivery rate of the energy can delay resistance formation in this organism.